Bonus babies? The impact of paid parental leave on fertility intentions - Fisher, Hayley; Bassford, Micaela (Sydney, 2016)
Paid parental leave has become an increasingly important part of family policy in OECD countries: by 2004 on average over a year of leave paid at 59% of average wages was provided. Australia’s Paid Parental Leave (PPL) scheme was introduced in 2011 and provides 18 weeks of leave paid at the full time minimum wage for the primary carer of a child. Prior to the scheme, federal and state legislation provided paid maternity leave for most state and federal employees. We estimate the effect of access to paid parental leave on women’s fertility desires and intentions by exploiting the differential impact of the scheme for women working in the public and private sectors. We find that the announcement of the scheme had no impact on fertility desires or intentions at the extensive margin but that, conditional on intending to have at least one (more) child, the number of children intended increases by 0.28, a 13% increase. This effect is driven by highly educated women who do not already have children. As it has been shown that fertility intentions predict fertility outcomes, these results suggest that even modest paid parental leave programs can increase the fertility of working women and so moderate the declines in fertility rates seen in many developed countries.
Economics Working Paper Series
Keywords: Employment -- Parental leave; Labour market; Employment; Parental leave; Employment and unemployment